THE STUDENTS PERCEPTION OF ENGLISH COURSES (THE NUTRITIONIST STUDY PROGRAM FACULTY OF HEALTH UNIVERSITAS NAHDLATUL ULAMA NUSA TENGGARA BARAT) - Lalu Dwi Satria Ardiansyah; Baiq Dewi Sukma Septiani; Fahimah Saifuddin (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2021)
The ability to use English is an important ability to be achieved in the process of learning a foreign language. The Nutritionist Study Program aims to develop students' language skills both orally and written. With oral skills, students are expected to master a number of vocabulary and sentence structures and be able to speak actively; With written skills, students are expected to be able to read and understand language texts, especially those closely related to the material being studied.This research was conducted to obtain data related to the perceptions of students of Nutritionist Study Program, Faculty of Health, UNU NTB.The learning process carried out, which is divided into five parts, namely: perceptions of English for the students, related Faculty of Health, UNU NTB: the purpose of learning English language proficiency, teaching materials from the language proficiency courses, application of language proficiency teaching methodologies, lecturers of English language proficiency courses perceptions and student perceptions of evaluation techniques used by lecturers of language proficiency courses in the Nutritionist Study Program, Faculty of Health, UNU NTB.The results of this study are expected be an evaluation material for the English learning process in the UNU NTB and future curriculum development.The ability to use English is an important ability to be achieved in the process of learning a foreign language. The Nutritionist Study Program aims to develop students' language skills both orally and written. With oral skills, students are expected to master a number of vocabulary and sentence structures and be able to speak actively; With written skills, students are expected to be able to read and understand language texts, especially those closely related to the material being studied.This research was conducted to obtain data related to the perceptions of students of Nutritionist Study Program, Faculty of Health, UNU NTB. The learning process carried out, which is divided into five parts, namely: perceptions of English for the students, related Faculty of Health, UNU NTB: the purpose of learning English language proficiency, teaching materials from the language proficiency courses, application of language proficiency teaching methodologies, lecturers of English language proficiency courses perceptions and student perceptions of evaluation techniques used by lecturers of language proficiency courses in the Nutritionist Study Program, Faculty of Health, UNU NTB. The results of this study are expected be an evaluation material for the English learning process in the UNU NTB and future curriculum development.Keywords:perception; process; learning; language proficiency